Hybrid wind power generation system controller - PMSG with fuel cell using fuzzy logic controller - Gunawan, Khairul; Putri, Raihan (Journal Geuthee of Engineering and Energy, 2023)
The increasing of the world energy demand affects energy source, especially in conventional energy will be scarce. Various of expert innovations emerge to exploit alternative energy as an energy source changing conventional energy. However, to produces electric power depend on energy source which is received, such as wind power system can produces electiric power if there is only wind velocity and fuel cell. Hybrid system integrates both of energy sources to increase the system power and reliability. This research simulates wind power system with fuel cell in the hybrid system. This simulation uses system modelling wiht the application of Simulink MATLAB ® R2014b. The system consists of wind power system that works parallel with fuel cell, electrolyzer, storage tube and hydrogen valve controlling the hydrogen flowing system, and also switching system. In this hybrid system, if the wind power system produces electric power exceeding the load of power demands, load will be supplied by wind power system and power that is excessive will be supplied to electrolyzer to be changed into hydrogen. Conversely, if the wind power system can not supply the load demands, fuel cell will produce electricity to minimize the lack of power in the system. Hybrid power system between wind power-PMSG and fuel cell using fuzzy logic controller works good enough so that the stability and continuity of energy is maintained with a percentage 12,5% occured due to transient conditions intermediate between the wind power system and fuel cell and voltage keep.